Real Estate Acquisition Tax versus Real Estate Transfer Tax in the Czech Republic. Past or Future? - Hrubá Smržová, Petra (Review of European and Comparative Law, 2022)
The real estate acquisition tax as a property transfer tax was part of the system of taxation of the Czech Republic until 25 September 2020.1 It was a traditional historical tax forming a complementary element of the system of taxation. Since 1993, it was part of the system of taxation as a real estate transfer tax. As of 1 January 2014, due to the recodification of private law, extensive tax reform came into effect, the scope of which was unprecedented since the 1990s. As a result, a new tax was introduced by the Statutory Measure of the Senate No. 340/2013 Coll., namely the real estate acquisition tax, which replaced the former real estate transfer tax. The new tax regulation preserved the taxation of real estate transfers upon payment in the form of the acquisition of immovable property, reflecting the changes brought about by the recodification of private law and by the new Business Corporations Act. It redefined the taxpayer entity, reduced the administrative complexity of tax administration, including cases of mandatory submission of expert reports for the purpose of determining the tax base, and updated the cases of exemption from the real estate acquisition tax.